Towards industrial robots as a service (IRaaS): Flexibility, usability, safety and business models - Buerkle, Achim; Eaton, William; Al-Yacoub, Ali; Zimmer, Melanie; Kinnell, Peter; Henshaw, Michael; Coombes, Matthew; Chen, Wen-Hua; Lohse, Niels (Robotics and computer-integrated manufacturing, 2023)
Industrial robots form an integral part of today's manufacturing industry, due to their high versatility, precision, and fatigue proof nature. Yet, many small and medium sized enterprises (SMEs) still predominantly rely on manual labor. The main barriers that prevent SMEs from utilizing robots to a larger degree are described to be the large initial investment, uncertainty about costs (total cost of ownership), and lack of expertise. An opportunity to eliminate these barriers can be found in servitisation. While paradigms such as software as a service (SaaS) or Robot as a Service (RaaS) already exist, these focus mostly on software (functionality) via cloud computing. In this paper, a new paradigm based on software and hardware is proposed as Industrial Robots as a Service (IRaaS), which is composed of four elements: Flexibility (Plug and Produce, mobility), Usability (Easy Programming, Intuitive Interaction), Safety (Standards, Strategies), and Business Models (Time-based, Usage-based). To provide an overview of the current state-of-the-art a scoping survey is performed on each of the four key elements from an IRaaS perspective.